Pengembangan Media Pembelajaran Multimedia Interaktif Berbasis Adobe Premiere Pro Pada Kompetensi Dasar Mengelola Kegiatan Humas Kelas XI Administrasi Perkantoran di SMK Negeri 2 Buduran Sidorajo - Muhammad Syamsudin Zaini; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this study is to find out an overview of the process of making interactive multimedia based on Adobe Premiere Pro on Basic Competence Managing Class XI Public Relations Activities Office Administration in SMK Negeri 2 Buduran Sidoarjo. This type of research uses the ADDIE (Analysis, Design, Develop, Implement, and Evaluate) research model, but the author only adopts 3 stages which include (Analysis), (Design), and (Develop). The results of the preliminary study indicate that student learning has previously used media in the learning process activities, but there are still shortcomings that will be complemented by using interactive learning media in the form of video animation based on Adobe Premiere Pro. This study shows the results that the product that has been produced is in the form of animated videos that contain material for Automation of Public Relations Governance and Basic Competence Protocol 4.1. Managing Class XII Public Relations Activities received very decent categories both in terms of material, graphic and included in the appropriate category for linguistic aspects. After going through some suggestions from experts who also stated that this media is interesting and facilitates the learning process of students in accordance with the results of media validation. With these results, the Development of Interactive Media Learning Media Based on Adobe Premiere Pro on Basic Competence in Managing Public Relations Activities in the XI Office Administration Office in SMK Negeri 2 Buduran Sidoarjo is feasible and can be used by students in learning Automation in Public Relations and Protocol Management.